2015
DOI: 10.18781/r.mex.fit.1507-1
|View full text |Cite
|
Sign up to set email alerts
|

Identification and antagonistic activity in vitro of Bacillus spp. and Trichoderma spp. isolates against common phytopathogenic fungi

Abstract: Identification and antagonistic activity in vitro af

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 18 publications
3
10
0
8
Order By: Relevance
“…The range of inhibition reported by several authors is broad, percentages of inhibition of 90 % are reported for B. subtilis strains against Fusarium sp. (Badía et al, 2011), and, on the other hand, percentages of inhibition of 29.4 % were reported for F. avenacum (Essghaier et al, 2012), and for B. methylotrophicus and B. amyloliquefaciens against F. oxysporum of 42.0 and 51.5 % (Rios et al, 2016); the latter are within the range obtained in this study. Strains CBMT2 and CBMT51 were the only ones to present halos of inhibition of mycelial growth in confrontation with F. equiseti with halos measuring 3.76 and 6.37 mm, respectively, which correspond to 18.3 and 31.5 % of inhibition ( Figure 1).…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…The range of inhibition reported by several authors is broad, percentages of inhibition of 90 % are reported for B. subtilis strains against Fusarium sp. (Badía et al, 2011), and, on the other hand, percentages of inhibition of 29.4 % were reported for F. avenacum (Essghaier et al, 2012), and for B. methylotrophicus and B. amyloliquefaciens against F. oxysporum of 42.0 and 51.5 % (Rios et al, 2016); the latter are within the range obtained in this study. Strains CBMT2 and CBMT51 were the only ones to present halos of inhibition of mycelial growth in confrontation with F. equiseti with halos measuring 3.76 and 6.37 mm, respectively, which correspond to 18.3 and 31.5 % of inhibition ( Figure 1).…”
Section: Resultssupporting
confidence: 90%
“…The biotests were carried out by direct confrontation with the widely used dual planting (Li et al, 2011;Essghaier et al, 2012;Rios et al, 2016). In the center of 90 x 15 mm Petri dished with potato dextrose agar (PDA) medium, we placed a disc, 0.5 cm in diameter, of mycelium of the pathogen with 10 d of active growth, and innoculated 6 µL of a 1x10 8 UFC bacterial solution in four equidistant points around the mycelial growth at a distance of 2 cm.…”
Section: Inhibition Of Mycelial Growth In Vitro Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…Aunque algunos fungicidas específicos han logrado reducir la severidad de la enfermedad en forma rápida y efectiva, su uso indiscriminado ha ocasionado la aparición de cepas resistentes y contaminación al ambiente (Qi et al, 2012). Por lo anteriormente señalado, en la actualidad para el manejo de Phytophthora se han considerado nuevas alternativas, basadas en el control biológico, estrategia importante en el manejo de fitopatógenos que habitan en el suelo, ya que reducen la aplicación de agroquímicos (Nguyen et al, 2012;Rios-Velasco et al, 2016).…”
Section: Resumen El Oomiceto Phytophthora Capsiciunclassified
“…Los mecanismos de control incluyen la producción de has led to the emergence of resistant isolates and environmental pollution (Qi et al, 2012). For this reason, new alternatives based on biological control are being considered for managing Phytophthora, an important strategy in soil-borne phytopathogen management, since they reduce the application of agrochemicals (Nguyen et al, 2012;Rios-Velasco et al, 2016). Different microorganisms have been reported to suppress P. capsici growth, including Streptomyces spp.…”
Section: Resumen El Oomiceto Phytophthora Capsicimentioning
confidence: 99%